XBP1u Is Involved in C2C12 Myoblast Differentiation via Accelerated Proteasomal Degradation of Id3 - Hayashi, Satoko; Sakata, Shotaro; Kawamura, Shotaro; Tokutake, Yukako; Yonekura, Shinichi (Frontiers in Physiology, 2022)
Myoblast differentiation is an ordered multistep process that includes withdrawal from the cell cycle, elongation, and fusion to form multinucleated myotubes. Id3, a member of the Id family, plays a crucial role in cell cycle exit and differentiation. However, in muscle cells after differentiation induction, the detailed mechanisms that diminish Id3 function and cause the cells to withdraw from the cell cycle are unknown. Induction of myoblast differentiation resulted in decreased expression of Id3 and increased expression of XBP1u, and XBP1u accelerated proteasomal degradation of Id3 in C2C12 cells. The expression levels of the cyclin-dependent kinase inhibitors p21, p27, and p57 were not increased after differentiation induction of XBP1 KD C2C12 cells. Moreover, knockdown (KD) of Id3 rescued myogenic differentiation of XBP1 KD C2C12 cells. Taken together, these findings provide evidence that XBP1u regulates cell cycle exit after myogenic differentiation induction through interactions with Id3. To the best of our knowledge, this is the first report of the involvement of XBP1u in myoblast differentiation. These results indicate that XBP1u may act as a “regulator” of myoblast differentiation under various physiological conditions.